ON THE STABLE SPHERICALLY-SYMMETRIC CHARGED DUST CONFIGURATIONS IN GENERAL RELATIVITY - Gladush, V. D. (Одеські астрономічні публікації, 2007)
The radial motion of a self-graviting charged dust and stability condition of the static charged dust spheres are considered. The stability is possible for the bound states of the weakly charged layer with abnormal charge with respect to the active mass.